Citizenship and human rights education in rural areas - Sousa, Rodger Roberto Alves de; Nascimento, Eriksen da Silva (Revista Interseção, 2025)
ABSTRACT Education in rural areas is a relevant topic for sustainable development and the promotion of social justice. Through professional training and development, valuing cultural traditions, access to technology, and educational inclusion, it is possible to guarantee agricultural and rural development. Moreover, citizenship and human rights education are fundamental to promote the active participation of farmers and rural workers in the political and social life of the country, as well as to strengthen democracy and social justice. Challenges and obstacles for education in rural areas include the lack of adequate infrastructure, social and educational exclusion, as well as the lack of effective public policies for promoting education in rural areas. It is necessary to invest in pedagogical strategies and methodologies that take into account the specificities of the rural context to ensure quality and effectiveness of education. Keywords: Rural education 1. Rural development 2. Citizenship 3. Human rights 4. Educação para a cidadania e direitos humanos no campo RESUMO A educação no campo é um tema relevante para o desenvolvimento sustentável e a promoção da justiça social. Através da formação e capacitação profissional, valorização das tradições culturais, acesso à tecnologia e inclusão escolar, é possível garantir o desenvolvimento agrícola e rural. Além disso, a educação para a cidadania e direitos humanos é fundamental para promover a participação ativa dos agricultores e trabalhadores rurais na vida política e social do país, bem como para o fortalecimento da democracia e da justiça social. Os desafios e obstáculos para a educação no campo incluem a falta de infraestrutura adequada, a exclusão social e educacional, bem como a falta de políticas públicas efetivas para a promoção da educação no campo. É necessário investir em estratégias e metodologias pedagógicas que levem em conta as especificidades do contexto rural, a fim de garantir a qualidade e efetividade da educação. Palavras-chave: Educação no campo. Desenvolvimento rural. Cidadania. Direitos humanos.